Hazard Normalization at Sea: Risk Perception and Osh Compliance Among Small-Scale Fishers in Jeneponto Regency - Yusriyanto; Romansyah Sahabuddin; Syamsu A Kamaruddin; Arlin Adam (Cendekiawan Indonesia Timur, 2026)
Small-scale fishing is crucial for global food security yet remains one of the most hazardous occupations. Despite constant exposure to environmental dangers, the relationship between fishers’ risk perception and their compliance with Occupational Safety and Health (OSH) practices remains underexplored. This study investigates this dynamic through the lens of the sociology of risk, viewing hazards not as objective probabilities but as socially constructed phenomena. For small-scale fishers, risk perception is deeply embedded in social norms, religious beliefs, and economic pressures. Dangers are often interpreted as inevitable fate rather than critical threats—a process of